Risk Factors Associated With 55 1 In Elective Gastrointestinal Surgery: A Prospective Study In A Specialized Surgical Centre - Joarder, Aminul Islam; Faruque, Mohammad Salahuddin; Elahi, M Nur E; Jahan, Ishrat; Siddiqui, Omar; Siddiqui, Md Muniruzzaman; Mubin, Samia; Imdad, Sadia; Hasan, Rakibul (Journal of Surgical Sciences, 2019)
Background: Understanding SSI and providing feedback to the surgical team has been shown to reduce the incidence of surgical site infection and the cost incurred due to it. Objective: To assess the risk factors of surgical site infection (SSI) in elective gastrointestinal surgery. Methods: prospective data were collected on 1122 surgical patients admitted in the surgery department in BSMMU from January 201 0 to July 201 2. All preoperative risk factors were evaluated .Patients operated were followed in the post operative period and if any wound infection noted, swab from the site of infection was sent for culture and sensitivity and antibiotics were given accordingly. Results: The incidence of SSI was 1 83(1 6.31 %).Out of this 1 83 cases 65.6% had BMI <25. Anaemia was present in 45.90% cases, bronchopulomnary disease was present in 1 1 .5% cases and DM & jaundice was present in 8.1 9% and 28.9% cases accordingly. 69(37.7%) cases were habitual smoker.SSI rate progressively increased with rate of contamination and maximum infection occurred in lower GIT surgery which was 144(1 7.84%). SSI developed more, in 1 02 (55.74 %) cases when duration of peration was more th ;1 1 1;1.2 hours. In 73.8% cases of SSI drain tube was used. Statistically significant risk factors for SS were found to be smoking habit, BMI <25, preoperative anaemia and duration of operation more than two hours. Conclusion: Specific optimization of the patients' preoperative condition is essential to reduce the risk of SSI following elective gastrointestinal surgery. Surveillance should be conducted and maintained in all hospitals to promote better surgical outcomes. Cessation of smoking, optimization of nutritional status, correction of anaemia and reduction of operation time should be associated with a lower incidence of SSI. Journal of Surgical Sciences (2012) Vol. 16 (2) : 71-75